NOAC monotherapy in patients with concomitant indications for oral anticoagulation undergoing transcatheter aortic valve implantation - Geis, Nicolas; Kiriakou, Christina; Chorianopoulos, Emmanuel; Katus, Hugo; Bekeredjian, Raffi (Clinical research in cardiology, 2018)
AimsAntithrombotic therapy after transcatheter aortic valve implantation (TAVI) is highly controversial and guideline recommendations are not evidence based. We assessed efficacy and safety of non-vitamin K antagonist oral anticoagulant (NOAC) monotherapy in patients with concomitant indications for OAC undergoing TAVI.MethodsAmong more than 1300 TAVI patients since 2008, 154 patients were identified who received postinterventional NOAC monotherapy. Outcomes were compared to 172 patients treated with vitamin K antagonist (VKA) monotherapy. Thromboembolic as well as bleeding complications were analysed for 6 months after TAVI.ResultsDespite high CHA2DS2-Vasc (4.6 ± 1.2), HEMORR2HAGES (4.7 ± 1.9) and HASBLED (2.7 ± 0.8) scores only three major/life-threatening bleedings and four thromboembolic events occurred after NOAC therapy had been initiated post-TAVI. 12 patients (7.8%) died within 6 months after the procedure. Compared to patients being treated with VKA monotherapy, analysis of a combined end-point of post-procedural death, stroke, embolism and severe bleeding revealed no significant differences (17/154 vs. 14/172; p = 0.45).ConclusionsThe results of this study suggest that NOAC therapy without additional antiplatelet treatment is effective and safe in patients with concomitant indications for OAC undergoing TAVI.